Efforts to Improve Islamic Religious Education Learning Outcomes through Sharing Models and Audio Visual Media at SMP Negeri 2 Sipispis - Purba, Yusnar; Nuruddin, Ahmad; Khairuddin; Harahap, Maya Sriyanti; Sarti (MANDAILING GLOBAL EDUKASIA, 2024)
This study aims to improve learning outcomes in Islamic Religious Education (PAI) through the application of a sharing learning model and the use of audio-visual media. The sharing model allows students to interact, discuss, and share understanding with peers, while audio-visual media plays a role in clarifying abstract concepts, so that learning becomes more interesting, interactive, and easy to understand. The research method used is classroom action research (CAR) with a qualitative and quantitative approach. The subjects of the study consisted of students who had difficulty understanding PAI material when using conventional methods. Data collection was carried out through observation, interviews, and learning outcome tests before and after the implementation of the method. The results of the study showed a significant increase in students' understanding of PAI material. This is reflected in the increase in students' average scores, increased active participation in class discussions, and increased learning motivation. In addition, students become more confident in expressing their opinions, more active in discussions, and have the courage to exchange ideas with classmates. Another advantage of this method is its ability to develop students' critical and collaborative thinking skills. Thus, the application of the sharing model combined with audio-visual media has proven to be an effective learning strategy in improving PAI learning outcomes. This method also creates a more dynamic, enjoyable learning environment and increases student involvement in the overall learning process